2008
DOI: 10.1021/ja806352v
|View full text |Cite
|
Sign up to set email alerts
|

An Entrant of Smaller Fullerene: C56 Captured by Chlorines and Aligned in Linear Chains

Abstract: A smaller fullerene C56 (#913) is stabilized, isolated, and crystallographically characterized as C56Cl10. The geometric parameters of C56Cl10 imply the otherwise unstable cage of C56 can be stabilized by chlorination through releasing its surface strains and maintaining fragmental aromaticity. An unexpected C Cl...ClC short contact, as well as the linear alignment with pearl-necklace-shaped, is revealed in C56Cl10 crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 29 publications
2
45
0
5
Order By: Relevance
“…It is known that the open-circuit voltage (V oc ) of a fullerene-based organic solar cell depends heavily on the HOMO level of the polymer donor and the LUMO level of the fullerene acceptor. As a useful electron-acceptor material, the fullerene derivative of 1-(3-methoxycarbonyl) propyl-1-phenylA C H T U N G T R E N N U N G [6,6] C 61 (PC 60 BM) has been employed widely in P3HT:PC n BM bulk heterojunction solar cells. [28] However, the LUMO of PC 60 BM is too low to prepare a P3HT:PC 60 BM bulk heterojunction solar cell with higher V oc .…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…It is known that the open-circuit voltage (V oc ) of a fullerene-based organic solar cell depends heavily on the HOMO level of the polymer donor and the LUMO level of the fullerene acceptor. As a useful electron-acceptor material, the fullerene derivative of 1-(3-methoxycarbonyl) propyl-1-phenylA C H T U N G T R E N N U N G [6,6] C 61 (PC 60 BM) has been employed widely in P3HT:PC n BM bulk heterojunction solar cells. [28] However, the LUMO of PC 60 BM is too low to prepare a P3HT:PC 60 BM bulk heterojunction solar cell with higher V oc .…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…And compared to the IPR-satisfying C 60 , many hydrides and fluorides of IPR-violating C 60 [16,17] were calculated to be more energetically stable. Besides, experimental investigations have also suggested that C 20 H 20 [18], C 50 Cl 10 [19], and C 56 Cl 10 [20] were energetically stable. For non-IPR fullerene derivatives, both theoretical and experimental investigations reported previously revealed that it was necessary to saturate all the active sites (the carbons atoms shared by two or three pentagons) [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[35] Recently, it has been demonstrated that in situ chlorination during classical fullerene synthesis offers valuable opportunities by effectively capturing various intermediates, thereby allowing for their isolation and structural characterization. Thus, besides a plethora of new interesting fullerenes species, [36][37][38][39][40][41][42] numerous perchlorinated polycyclic aromatic hydrocarbons (PAHs) have been identified by utilizing this process. [43][44][45][46][47][48] The spectrum of isolated products served as the first experimental support for the pentagon road (PR) model of fullerene formation.…”
Section: Introductionmentioning
confidence: 99%